Investment, Poverty and Growth Nexus in Pakistan: Empirical Evidence from ARDL Modeling Approach to Co-Integration - Ali, Hina; Sharif, Imran (Journal of Quantitative Methods, 2020)
This study analyzes the nexus of investment, poverty and growth in Pakistan. It will develop comprehensive macro economic model of Pakistan economy with the desire of amplification and provided that a long-term result for the determined investment-poverty-growth discrepancy veterans. The significant level of investment and sustained economic growth may be the major driving forces for poverty decrease in Pakistan. The level of investment also assists the poor through a direct allocation influence as well as tortuous growth effect, in both the long run and short run. To detect the long term and short term effects of economic development, poverty and investment, an ARDL modeling approach to co- integration is functional, which is the suitable technique in excess of method of integration after examining the stationary level of the data through ADF Test. The bound testing approach is exploited for cointegration to analyze the presence of long term association amid variables and ECM models are verbalized for short term analysis. The model is predictable with time-series data from 1972 to 2013 confine mutually the long-run and short-run forceful goods of the economy. The model is subjected to a sequence of strategy situation that assesses a mixture of options for government to recover the prolific ability of the economy, thus attain continued hasten growth and a decrease in Pakistan`s poverty. JEL Classification Codes: G12, G 14